Detection of circulating microRNAs with Ago2 complexes to monitor the tumor dynamics of colorectal cancer patients during chemotherapy. Issue 9 (7th January 2019) - Fuji, Tomokazu; Umeda, Yuzo; Nyuya, Akihiro; Taniguchi, Fumitaka; Kawai, Takashi; Yasui, Kazuya; Toshima, Toshiaki; Yoshida, Kazuhiro; Fujiwara, Toshiyoshi; Goel, Ajay; Nagasaka, Takeshi
Abstract : Because of the different forms of circulating miRNAs in plasma, Argonaute2 (Ago2)‐miRNAs and extracellular vesicles (EV‐miRNAs), we examined the two forms of extracellular miRNAs in vitro and developed a unique methodology to detect circulating Ago2‐miRNAs in small volumes of plasma. We demonstrated that Ago2‐ miR‐21 could be released into the extracellular fluid by active export from viable cancer cells and cytolysis in vitro . As miR‐21 and miR‐200c were abundantly expressed in both metastatic liver sites and primary lesions, we evaluated Ago2‐ miR‐21 as a candidate biomarker of both active export and cytolysis while Ago2‐ miR‐200c as a biomarker of cytolysis in plasma obtained from colorectal cancer (CRC) patients before treatment and in a series of plasma obtained from CRC patients with liver metastasis who received systemic chemotherapy. The measurement of Ago2 ‐miR‐21 allowed us to distinguish CRC patients from subjects without CRC. The trend in ΔCt values for Ago2 ‐miR‐21 and ‐200c during chemotherapy could predict tumor response to ongoing treatment. Thus, capturing circulating Ago2‐miRNAs from active export can screen patients with tumor burdens, while capturing them from passive release by cytolysis can monitor tumor dynamics during chemotherapy treatment. Abstract : What's new? Ago2‐associated miRNAs can either be released by cytolysis or actively booted out of the cell. In our study, the authors showed which Ago2‐complexed miRNAs are released by the different mechanisms. Because viable cancer cells release Ago‐miRNA‐21, it could serve as a biomarker to indicate the presence of cancer. Here, the authors used Ago‐miRNA‐21 to detect the presence of colorectal cancer. Conversely, Ago2‐miR‐200c appears in the bloodstream after cytolysis, and may indicate how well chemotherapy is killing tumor cells. The relationship between the two miRNAs could provide a window into tumor dynamics during treatment.